Role of Prenatal Hypoxia in Brain Development, Cognitive Functions, and Neurodegeneration - Nalivaeva, Natalia N.; Turner, Anthony J.; Zhuravin, Igor A. (Frontiers in Neuroscience, 2018)
This review focuses on the role of prenatal hypoxia (PH) in the development of brain functions in the postnatal period and subsequent increased risk of neurodegenerative disorders in later life. Accumulating evidence suggests that PH in critical periods of brain formation results in significant changes in development of cognitive functions at various stages of postnatal life. They correlate with morphological changes in brain structures involved in learning and memory as well as with a decrease in brain adaptive potential and plasticity caused by disturbances in the process of formation of new contacts between cellular populations and propagation of neuronal stimuli, especially in the cortex and hippocampus. On the other hand, PH has a significant impact on expression and processing of a variety of genes involved in normal brain function and their epigenetic regulation. Among proteins affected by PH are a key enzyme of the cholinergic system - acetylcholinesterase, and the amyloid precursor protein (APP), both of which have important roles in brain functioning. Disruption of their expression and metabolism caused by PH can result, apart from early cognitive dysfunctions, also in development of neurodegeneration in later life. Another group of enzymes involved in catabolism of neuropeptides, including amyloid-β peptide (Aβ), are also affected by PH. The decrease in the activity of neprilysin and other amyloid-degrading enzymes after PH could result over the years in an Aβ clearance deficit and accumulation of its toxic species causing neuronal cell death and development of neurodegeneration. Applying various approaches to restore expression of neuronal genes disrupted by PH during postnatal development opens an avenue for therapeutic compensation of cognitive dysfunctions and prevention of Aβ accumulation in the ageing brain and the model of PH in rodents can be used as a reliable tool for assessment of their efficacy.